2015
DOI: 10.1007/s13277-015-3533-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative platelet/lymphocyte ratio is a superior prognostic factor compared to other systemic inflammatory response markers in ovarian cancer patients

Abstract: The aim of the present study was to determine the most meaningful preoperative prognostic factor of cancer-related death in ovarian cancer patients by comparing potentially prognostic systemic inflammatory response (SIR) markers. The levels of fibrinogen, albumin, C-reactive protein (CRP), and serum cancer antigen-125 (CA-125) and the neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) were evaluated in 190 ovarian cancer patients to identify predictors of overall survival (OS) and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 40 publications
4
95
0
3
Order By: Relevance
“…The NOS scores, which indicated the quality of these studies, ranged from 6 to 8. Five of the selected eligible studies presented data regarding the association between the PLR and OS [14][15][16][17][18] , five studies discussed the link between PLR and PFS [15][16][17][18][19] , and six examined numerical differences in PLR between patients with malignant ovarian masses and the controls [20][21][22][23][24][25] . The disease characteristics in 12 studies are summarized in Table 2.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NOS scores, which indicated the quality of these studies, ranged from 6 to 8. Five of the selected eligible studies presented data regarding the association between the PLR and OS [14][15][16][17][18] , five studies discussed the link between PLR and PFS [15][16][17][18][19] , and six examined numerical differences in PLR between patients with malignant ovarian masses and the controls [20][21][22][23][24][25] . The disease characteristics in 12 studies are summarized in Table 2.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Five studies comprising 1051 patients investigated the association between PLR and PFS [15][16][17][18][19] . High PLR indicated an inferior PFS outcome, with a combined HR of 1.61 (95% CI 1.03-2.51, p < 0.01) (Figure 3), which indicated that patients with a higher PLR had a higher risk of disease progression than those with a low PLR.…”
Section: Plr and Pfs In Ovarian Cancermentioning
confidence: 99%
“…A number of inflammation markers have been evaluated to stratify patients for treatment and to predict survival (9). The prognostic value of preoperative systemic inflammationrelated neutrophil-lymphocyte ratio (NLR) and plateletlymphocyte ratio (PLR) has been demonstrated in patients with a variety of cancers (10)(11)(12)(13)(14)(15)(16)(17)(18). However, no previous studies have evaluated the association between NLR and PLR with the prognosis of thymic tumors.…”
Section: Original Articlementioning
confidence: 99%
“…[11]. Furthermore, Zhang and colleagues presumed that preoperative PLR was superior to the other SIR markers (CA-125, NLR, fibrinogen, CRP, and albumin) as a predictor of survival in ovarian cancer patients [7]. Although several studies investigated the association between preoperative NLR and PLR with invasive ovarian cancers, to the best of our knowledge, there were no reported studies in the literature which researched these markers in the BOTs.…”
Section: Discussionmentioning
confidence: 99%
“…As preoperative inflammatory markers, neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been suggested to be useful for discriminating malignant and benign ovarian tumors. NLR and PLR are noninvasive, easily measured, universally known and cost-effective markers [57]. …”
Section: Introductionmentioning
confidence: 99%